Guadua zuloagae sp. nov., the first petrified bamboo culm record from the Ituzaingó Formation (Pliocene), Paraná Basin, Argentina - Brea, Mariana (2007)
• Background and Aims: The anatomical characterization and morphology of Guadua zuloagae nov. sp. (Poaceae-Bambusoideae) culm was determined. This material was collected at the Toma Vieja fossil locality, Paraná basin, Argentina. This fossil culm is the first record of Bambusoideae in sediments of the Pliocene from the Ituzaingó Formation. The studied specimen was compared with the taxa of the Bambusoideae sub-family, especially with the American woody bamboos and others taxa that have woody culms, including Arundo, Thysalonaena and Gynerium. • Methods: The material was preserved by siliceous cellular permineralization, and it was prepared for microscopic examination by surface polishing and thin sections. The morphology and anatomy of this new species were described. The estimated height, critical buckling height and safety factor were calculated on the basis of the fossil bamboo diameter using the formula of Niklas. The relationship and comparison with the nearest living relatives (NLRs) are discussed. • Key Results: Well-preserved petrified culm with internodes and nodes from the Pliocene of Argentina provides the basis for the description of a new fossil bamboo, Guadua zuloagae. The results of the anatomical analysis of the fossil bamboo showed a great affinity with the extant species Guadua angustifolia and constitute the first evidence of petrified bamboo culm. • Conclusions: The new fossil bamboo culm constitutes the only fossil record, preserved as permineralized by silicification, in the world. This fossil record indicates that the genus Guadua was more widespread in the past than today. Discovery of G. zuloagae allows the presence of a Bambusoideae understorey in the mixed forests described for the Ituzaingó Formation to be inferred. The climatic conditions inferred from fossil bamboo and sedimentary deposits indicate a temperate-warm, humid climate.